2021
DOI: 10.4271/03-15-05-0033
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Gasoline Partially Premixed Combustion with External Exhaust Gas Recirculation

Abstract: The stringent emission regulations for Internal Combustion Engines (ICEs) spawned a great amount of research in the field of innovative combustion approaches characterized by high efficiency and low emissions. Previous research demonstrate that such promising techniques, named Low-Temperature Combustion (LTC), combine the benefits of Compression Ignition (CI) engines, such as high compression ratio and unthrottled lean mixture, with low engine-out emissions using a properly premixed air-fuel mixture. Due to lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 28 publications
0
18
0
1
Order By: Relevance
“…It is important to highlight that GCI combustion typically works with high EGR rates to limit pollutants [15,18], and its impact on the ignition delay (and consequently on SOC) is remarkable. Previous works made by the authors demonstrated that to make stable and reliable GCI combustion, a very strong first combustion stage (related to the combustion of the pilot injections) is mandatory even using high EGR rates [13,20]. As a result, during the whole experimental activity the EGR system has been turned off mainly because its effects on the first combustion stage is negligible in terms of energy released, and consequently on the signalto-noise ratio.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…It is important to highlight that GCI combustion typically works with high EGR rates to limit pollutants [15,18], and its impact on the ignition delay (and consequently on SOC) is remarkable. Previous works made by the authors demonstrated that to make stable and reliable GCI combustion, a very strong first combustion stage (related to the combustion of the pilot injections) is mandatory even using high EGR rates [13,20]. As a result, during the whole experimental activity the EGR system has been turned off mainly because its effects on the first combustion stage is negligible in terms of energy released, and consequently on the signalto-noise ratio.…”
Section: Methodsmentioning
confidence: 99%
“…As documented in literature [18][19][20][21]27], GCI combustion needs high boost pressure and intake temperature to promote the gasoline autoignition. This aspect becomes crucial especially during cranking, idle or at low loads when the exhaust gas energy is not enough to drive the turbocharger reaching the target value of boost pressure.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Conventional CI engines operating on diesel fuel have high thermal efficiency, but they suffer from high soot emissions and NOx due to heterogeneous fuel air mixtures and high combustion temperatures. 2 In order to achieve the best of both combustion modes, several advanced concepts like homogeneous charge compression ignition (HCCI) 3,4 reactivity controlled compression ignition (RCCI) [5][6][7] ,gasoline compression ignition (GCI), 8,9 partially premixed combustion (PPC), 10,11 etc. have been proposed in the literature.…”
Section: Introductionmentioning
confidence: 99%